1985
DOI: 10.1177/096032718500400205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Anticonvulsant Monotherapy on Lymphocyte Subpopulations in Adult Epileptic Patients

Abstract: Sixty-five patients undergoing long-term monotherapy for at least 3 months with phenytoin, carbamazepine or phenobarbital were screened for lymphocyte and immunoglobulin abnormalities. In 57% of patients the duration of therapy was longer than 12 months. The control subjects were matched for sex and age and none of them was taking drugs. The average serum immunoglobulin (IgG, IgA, IgM) values did not differ in control and patient groups. A significant decrease of OKT4+ cells was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…The results of prospective studies have clearly demonstrated that PHT can induce a humoral immune response deficiency (Seager et al, 1975;Bardana et al, 1983;Marcoli et al, 1985;Ricevuti et al, 1986). At present, more is known about the effect of PHT on the immune system than is known about any other AED (Aarli and Gilhus, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…The results of prospective studies have clearly demonstrated that PHT can induce a humoral immune response deficiency (Seager et al, 1975;Bardana et al, 1983;Marcoli et al, 1985;Ricevuti et al, 1986). At present, more is known about the effect of PHT on the immune system than is known about any other AED (Aarli and Gilhus, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated a slightly reduced number of T cells and T cell subpopulations and a reduced response to T cell mitogens when examining cells from epileptic patients on various anti-epileptic drugs (7,lO-12). Patients on CBZ monotherapy have a slightly reduced proportion of OKT3+ and OKT4+ cells (13). However, epileptic patients who have not received any drug treatment have the same reduction of T cells and T cell mitogen responses when compared to controls (14).…”
Section: Discussionmentioning
confidence: 97%
“…Suppressor T cells are increased in patients with panhypogammaglobulinaemia (Dosch et al 1982;Lillie et al 1983), while a significant reduction in suppressor T cells was found in patients with a significant rise in serum IgM levels (Basaran et al 1989). T helper lymphocytes were significantly reduced in another study (Marcoli et al 1985). Once again, there is a discrepancy between clinical findings and in vitro studies, where incubation of mononuclear cells from healthy donors with phenytoin 20 mg/L did not induce changes in T regulator lymphocytes (Gilhus 1984).…”
Section: Phenytoinmentioning
confidence: 88%
“…To make the picture more confusing, several studies have found normal (Basaran et al 1989;Burks et al 1989;Eeg-Olofsson et al 1986;Marcoli et al 1985;Meissner et al 1983) or even increased (Valli et al 1982) serum IgA levels. These discrepancies are not easily explained.…”
Section: Phenytoinmentioning
confidence: 99%